Fiqh Learning For Elementary School Students in Kutamakmur North Aceh: A Study on Studentsâ Ability in Learning Shalat - Latif, Umar; Nurainiah, Nurainiah (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
Fiqh learning is a part of learning process in PAI (Islamic Education) subject given to students especially the elementary ones. It is the responsibility of all teachers and parents to provide the childrenâs needs, clothing, as well as Islamic education. However, from the field observation, some of parents pay little attention to their childrenâs religious education as if such education were only the responsibility of formal educational institution. This present research aims to investigate what the level of elementary school studentsâ understanding on shalat is, how the process of fiqh learning is conducted, and what obstacles the teacher encounter in this learning. This research uses analytical descriptive method with the approach of library research and field research. The data were collected through observation, interview, and field research. The findings of this research reveal that some students in 2 elementary schools; SDN 2 and SDN 6 have not yet understood the concept of shalat; some of them are not able to recite and memorize doâa in. On the other hand, students in SDN 1 Kutamakmur has understood the concept and process of shalat and are able to recite and memorize doâa in shalat. The process of fiqh learning in SDN 2 and SDN 6 Kutamakmur North Aceh has not yet run properly because some students are not able to memorize doâa in shalat as it is expected. The obstacles the teachers encounter is the limited time availability to do practice in school, the lack of parentsâ guidance in teaching and urging their children to do shalat. Hence, students only learn this at school without parentsâ guidance and some of students are not able to recite and memorize doâa in shalat.